2011
DOI: 10.1155/2011/952956
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Coma Scale and Its Components on Admission: Are They Valuable Prognostic Tools in Acute Mixed Drug Poisoning?

Abstract: Introduction. The verbal, eye, and motor components of Glasgow coma scale (GCS) may be influenced by poisoned patients' behavior in an attempted suicide. So, the values of admission GCS and its components for outcomes prediction in mixed drugs poisoning were investigated. Materials and Methods. A followup study data was performed on patients with mixed drugs poisoning. Outcomes were recorded as without complications and with complications. Discrimination was evaluated by calculating the area under the receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Poisoning with drugs influences the biochemical substances of the brain and causes brain damage. This may change the level of consciousness as well (Mood et al, 2011).In the current study there was statistically significant difference between discharged and died patients as regard GCS. There were 85% of died had GCS less than or equal to 8.…”
Section: Discussionmentioning
confidence: 43%
“…Poisoning with drugs influences the biochemical substances of the brain and causes brain damage. This may change the level of consciousness as well (Mood et al, 2011).In the current study there was statistically significant difference between discharged and died patients as regard GCS. There were 85% of died had GCS less than or equal to 8.…”
Section: Discussionmentioning
confidence: 43%
“…Although rapid changes in the level of consciousness in poisoning cases may raise a question of the role of GCS on admission in predicting outcome, Ezadi Mood and colleagues 22 showed that the admission GCS score as well as its components can be validated for poisoned patients with mixed drug ingestion.…”
Section: Resultsmentioning
confidence: 99%
“…This is surely the consequence of the high prevalence of benzodiazepines and other sedative drugs in our study. Nevertheless, the use of GCS remains controversial in acute poisoning because it is not strictly correlated with the risk of gastric aspiration, and there is no consensus on a threshold value that would mandate intubation .…”
Section: Discussionmentioning
confidence: 99%